Single-Cell Phenotypic and Molecular Characterization of Circulating Tumor Cells Isolated from Cryopreserved Peripheral Blood Mononuclear Cells of Patients with Lung Cancer and Sarcoma. (19th March 2022) - Vismara, Marta; Reduzzi, Carolina; Silvestri, Marco; Murianni, Fabio; Lo Russo, Giuseppe; Fortunato, Orazio; Motta, Rosita; Lanzoni, Davide; Giovinazzo, Francesca; Miodini, Patrizia; Pasquali, Sandro; Suatoni, Paola; et al.
Abstract: Background: The isolation of circulating tumor cells (CTCs) requires rapid processing of the collected blood due to their inherent fragility. The ability to recover CTCs from peripheral blood mononuclear cells (PBMCs) preserved from cancer patients could allow for retrospective analyses or multicenter CTC studies. Methods: We compared the efficacy of CTC recovery and characterization using cryopreserved PMBCs vs fresh whole blood from patients with non-small cell lung cancer (NSCLC; n = 8) and sarcoma (n = 6). Two epithelial cellular adhesion molecule (EpCAM)-independent strategies for CTC enrichment, based on Parsortix ® technology or immunomagnetic depletion of blood cells (AutoMACS ® ) were tested, followed by DEPArray™ single-cell isolation. Phenotype and genotype, assessed by copy number alterations analysis, were evaluated at a single-cell level. Detection of target mutations in CTC-enriched samples from frozen NSCLC PBMCs was also evaluated by digital PCR (dPCR). Results: The use of cryopreserved PBMCs from cancer patients allowed for the retrospective enumeration of CTCs and their molecular characterization, using both EpCAM-independent strategies that performed equally in capturing CTC. Cells isolated from frozen PBMCs were representative of whole blood-derived CTCs in terms of number, phenotype, and copy number aberration profile/target mutations. Long-term storage (≥3 years) did not affect the efficacy of CTC recovery. Detection of target mutations was also feasible by dPCR in CTC-enriched samples derived from stored PBMCs. Conclusions: Isolating CTCs from longitudinally collected PBMCs using an unbiased selection strategy can offer a wider range of retrospective genomic/phenotypic analyses to guide patients' personalized therapy, paving the way for sample sharing in multicenter studies.